Effects of inhaling essential oils of Citrus limonum L., Santalum album, and Cinnamomum camphora on human brain activity. Issue 2 (9th January 2023) - Ueda, Kazutaka; Horita, Tatsushi; Suzuki, Takeshi
Abstract: Introduction: Essential oil inhalation has various effects on the human body. However, its effects on cognitive function and the neural basis remain unclear. We aimed to investigate the effects of inhaling lemon, sandalwood, and kusunoki essential oils on human brain activity and memory function using multichannel electroencephalography and brain source activity estimation. Methods: Participants performed a letter 2‐back working memory task during electroencephalography measurements before and after essential oil inhalation. Brain activation, task difficulty, concentration degree, and task performance were compared among the essential oils and a fragrance‐free control. Results: Task performance significantly improved after lemon essential oil inhalation. Lemon essential oil inhalation resulted in delta and theta band activation in the prefrontal cortex, including the anterior cingulate gyrus and orbitofrontal cortex, superior temporal gyrus, parahippocampal gyrus, and insula. During inhalation, persistent alpha band activation was observed in the prefrontal cortex, including the anterior cingulate gyrus. Sandalwood essential oil inhalation led to beta and gamma band activation in the prefrontal cortex, including the anterior cingulate gyrus. Conclusion: Our findings demonstrate that different essential oils have specific effects on brain activity related to emotion and memory processing. Abstract :